The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1021/jp010094e
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Freezing of Aqueous Particles Induced by Crystallized (NH4)2SO4, Ice, and Letovicite

Abstract: Heterogeneous freezing of aqueous particles with solid inclusions of crystallized (NH 4 ) 2 SO 4 , ice, and letovicite were studied using optical microscopy and differential scanning calorimetry. For (NH 4 ) 2 SO 4 -H 2 O particles, the heterogeneous freezing temperature was found to be dependent on the morphology of the (NH 4 ) 2 SO 4 solid. If the crystallized solid was in the form of microcrystals, the heterogeneous ice-freezing temperature was close to the eutectic temperature and the critical saturation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 36 publications
4
95
0
Order By: Relevance
“…present work show rough surfaces that may be consistent with the ammonium sulfate microcrystals observed by Zuberi et al (2001) when they found low ice saturation ratios.…”
Section: Mixed-sample Experimentssupporting
confidence: 90%
See 1 more Smart Citation
“…present work show rough surfaces that may be consistent with the ammonium sulfate microcrystals observed by Zuberi et al (2001) when they found low ice saturation ratios.…”
Section: Mixed-sample Experimentssupporting
confidence: 90%
“…Using this experimental technique we are not able to precisely quantify how small surfaces defects may influence our results. However, work by Zuberi et al (2001) suggests that heterogeneous freezing temperatures in the immersion freezing mode are strongly dependent on surface morphology, specifically surface area and particle microstructure. Optical images of the solid ammonium sulfate particles used in the 8 F08 Fig.…”
Section: Mixed-sample Experimentsmentioning
confidence: 99%
“…Small embryos of ice might then survive in suited cavities or crevices at the particle surface even at relative humidities substantially below S ice = 1 and cause a lower threshold relative humidity for ice formation in a succeeding nucleation experiment. As an alternative interpretation, the ice crystals may imprint their structure on the surface of soft materials, yielding a surface structure that more closely resembles the ice lattice and that can then act as an activated site to promote ice nucleation (Vali, 2008;Zuberi et al, 2001). A pre-activation has also been observed for particles cooled to temperatures below 236 K and exposed to an environment with S ice <1 in order to explicitly avoid initial ice formation (Fukuta, 1966;Higuchi and Fukuta, 1966).…”
Section: Ice Nucleation Ability Of Sodium Oxalate Crystallisation Atmentioning
confidence: 99%
“…The impact of surface microstructure of crystalline solids on their heterogeneous freezing ability is well documented in the literature, as for example in the case of ammonium sulphate particles. Zuberi et al (2001) have demonstrated that the thermal history of solid ammonium sulphate cores imbedded in aqueous particles affected their morphology and heterogeneous ice nucleability. A crystalline core composed of many microcrystals, Infrared extinction spectra recorded from t = 85 s (spectrum a) to t = 125 s (spectrum e) at a 10 s time interval during expansion run 1 from Exp.…”
Section: Ice Nucleation Ability Of Oxalic Acid Dihydrate Crystallisamentioning
confidence: 99%
“…The physical state of aerosol particles is also important for their ability to act as cloud condensation nuclei (CCNs) and has been discussed in the context of cirrus cloud formation (Martin, 1998;Bertram et al, 2000;Zuberi et al, 2001). Although the ice nucleation process largely determines the microphysical properties of cirrus clouds and therefore their climate forcing potential (DeMott et al, 2001), the exact role of aerosol particles in cirrus formation remains unclear (Martin, 2000).…”
Section: Introductionmentioning
confidence: 99%